AGROWISATA PENGEMBANGAN SEKTOR PERTANIAN BUAH MELON DALAM MITIGASI RESESI EKONOMI DAMPAK PANDEMI COVID-19 - Mat Bahri; Aang Kunaifi; Ghufron (Ekosiana Jurnal Ekonomi Syari ah, 2021)
: The COVID-19 pandemic has presented real challenges in the economic field. Slowing commodity flows automatically stagnate various transactions, resulting in a financial recession. Therefore, the creativity of economic actors is required in responding to this matter. The agricultural sector also experienced the same slowdown, one of which was the production of melons. This article aims to explore and describe the form of melon fruit business development and its effectiveness in contributing to economic recession mitigation, especially for rural communities. The research method used in this article is qualitative. Data were collected through direct observation to the object and interviews with the farmers concerned. Furthermore, the data were analyzed with various theories about community economic empowerment. The results of research on the effectiveness of business development by increasing consumption and sales of melons through environmental conservation and increased production. While the economic contribution through the two strategies above is the economic empowerment of the surrounding community through the multiplier effect of environmental tourism or agro-tourism. Through this research, it is hoped that farmers will continue to increase the use value of agriculture and melon production. Externally, it is hoped that the regional government and the central government will establish appropriate and targeted regulations, in the form of access to capital and marketing. Keywords: Agriculture, Agrotourism, Recession Mitigation, Market Access, Community Empowerment. DAFTAR PUSTAKA Hs, Hendy Hendro, Zed Nahdi, MTh Sri Budiastuti, dan Djoko Purnomo. “PEMETAAN PARAMETER LAHAN KRITIS GUNA MENDUKUNG REHABILITASI HUTAN DAN LAHAN UNTUK KELESTARIAN LINGKUNGAN DAN KETAHANAN PANGAN DENGAN MENGGUNAKAN PENDEKATAN SPASIAL TEMPORAL DI KAWASAN MURIA.” Prosiding SNST Fakultas Teknik 1, no. 1 (2015). https://publikasiilmiah.unwahas.ac.id/index.php/PROSIDING_SNST_FT/article/view/1170. Kunaifi, Aang. “Empowerment Ekonomi Publik Dalam Mengatasi Resesi Dampak Pandemi.” Dalam Perspektif Multidisipliner dalam Pelaksanaan Adaptasi Kebiasaan Baru, 1 ed., 1:3–12. 1 1. Tulungagung: Akademia Pustaka, 2020. ———. “Telaah Kritis Kebijakan Fiskal Perspektif Kaidah Fiqh.” Proceedings International Seminar, 1, The 3rd Annual International on Islamic International Education, no. Vol.3 No.1 (2018): Seri-1 (26 Februari 2018): 21. Kunaifi, Aang, dan Lailatul Qomariyah. “Developing Company Images Through Spiritual Public Relations Facing Covid-19 Outbreak.” Jurnal Iqtisaduna 1, no. 1 (10 September 2021): 13–22. https://doi.org/10.24252/iqtisaduna.v1i1.15808. Kunaifi, Aang, Fadali Rahman, dan Risca Dwiaryanti. “The Philosophy and Authentication of Welfare Equalization in the Islamic Economy.” Jurnal Kajian Peradaban Islam 4, no. 2 (24 Juni 2021): 54–62. https://doi.org/10.47076/jkpis.v4i2.67. Kurniawan, Frans Hengky. “INCOME COMPARISON ON INTENSIFICATION AND NON INTENSIFICATION OF RUBBER FARMERS IN MONTERADO VILLAGE, MONTERADO DISTRICT, BENGKAYANG REGENCY KOMPARASI PENDAPATAN PETANI KARET INTENSIFIKASI DAN NON INTENSIFIKASI DI DESA MONTERADO KECAMATAN MONTERADO KABUPATEN BENGKAYANG.” AGRIBUSINESS JOURNAL 14, no. 1 (2 Juni 2020). https://doi.org/10.15408/aj.v14i1.16313. Kurniawan, Fuat Edi. “The Dilemma of Agricultural Mechanization and the Marginalization of Women Farmworkers in Rural Areas.” Sodality: Jurnal Sosiologi Pedesaan 9, no. 2 (18 Agustus 2021). https://doi.org/10.22500/9202132575. Mawardi, Ahmad Ahsin Kusuma. “Strategi Pengembangan Agrowisata Rembangan Jember Melalui Pendekatan Satisfaction Wisatawan,” 9 Juni 2016. http://repository.unej.ac.id/handle/123456789/74675. Nurhilmiah, Mia, Dadi Dadi, dan Awang Kustiawan. “IDENTIFIKASI PERSEPSI MASYARAKAT KUTA TENTANG KONSERVASI LINGKUNGAN.” Bioed : Jurnal Pendidikan Biologi 9, no. 1 (10 Mei 2021): 39–48. https://doi.org/10.25157/jpb.v9i1.5331. Putra, Adetiya Prananda`, Firda Rachma Amalia, dan Sari Wiji Utami. “STRATEGI PENGEMBANGAN AGROWISATA BERBASIS COMMUNITY BASED TOURISM DI DESA SUMBER ARUM KECAMATAN SONGGON BANYUWANGI.” UNEJ E-Proceeding, 11 Desember 2018. https://jurnal.unej.ac.id/index.php/prosiding/article/view/9206. Saputra, Sahran, dan Mujahiddin Mujahiddin. “STIMULUS AGROSOCIOPRENEUR MELALUI PENGEMBANGAN SISTEM REFUGIA DAN LEBAH MADU BERBASIS PERTANIAN JERUK DI DESA SEKOCI KABUPATEN LANGKAT.” JMM (Jurnal Masyarakat Mandiri) 5, no. 4 (1 Agustus 2021): 1689–1700. https://doi.org/10.31764/jmm.v5i4.4902. Saputra, Taufik Aris, Aang Kunaifi, dan Siti Azizah. “DIVERSIFIKASI PRODUK PENDEKATAN ISLAMIC ETHIC DALAM MENINGKATKAN OMSET BISNIS RETAIL.” CENDEKIA: Jurnal Studi Keislaman 7, no. 1 (9 Juli 2021): 1–16. Tinov, M. Y. Tiyas, dan Tito Handoko. “PERAN SERTA MASYARAKAT DALAM KONSERVASI LINGKUNGAN PASCA AKTIVITAS PERTAMBANGAN TANPA IZIN (PETI) DI DESA KOTO CERENTI KECAMATAN CERENTI KABUPATEN KUANTAN SINGINGI.” Jurnal Pengabdian Kepada Masyarakat 2, no. 4 (4 April 2018): 363–66. Wirakusuma, Gilang. “APA YANG MENDORONG DIVERSIFIKASI PENDAPATAN PETANI?: TINJAUAN EMPIRIS RUMAH TANGGA TANI PADI PROVINSI JAWA TIMUR.” Agrisocionomics: Jurnal Sosial Ekonomi Pertanian 4, no. 1 (27 Mei 2020): 135–46. https://doi.org/10.14710/agrisocionomics.v4i1.6091. Yandri, Lara Indra, dan Immu Puteri Sari. “STRATEGI PEMBANGUNAN PEDESAAN BERBASIS PERTANIAN LAHAN BASAH DI NAGARI SUNGAI RIMBANG KECAMATAN SULIKI KABUPATEN LIMA PULUH KOTA.” Menara Ilmu 13, no. 11 (22 Oktober 2019). https://doi.org/10.31869/mi.v13i11.1644.